Impact of a persuasive antimicrobial stewardship programme on the appropriateness of surgical antimicrobial prophylaxis in a tertiary care hospital in southern Italy - Lorenzo Onorato; Margherita Macera; Caterina Curatolo; Viraj Pattapola; Verdiana Zollo; Caterina Monari; Federica Calò; Pasquale Di Girolamo Faraone; Ferdinando Russo; Nicola Coppola (Journal of Global Antimicrobial Resistance)
Background and aim: The aim of our study was to evaluate the rate of compliance to institutional guidelines on surgical antimicrobial prophylaxis (SAP) among the surgical wards of our facility and to evaluate the impact of our antimicrobial stewardship programme (ASP) on the adherence rate. Methods: We conducted a cross-sectional study including all 14 surgical wards of our hospital. Eight of these wards participate in a non-restrictive ASP. All patients admitted to one of the wards who had been prescribed SAP were included; the appropriateness of prophylaxis was defined according to the institutional protocols. Results: During the study period, we evaluated 169 patients undergoing a surgical procedure, of whom 105 (62.1%) received SAP. Overall, 10 (10.5%) patients were prescribed unnecessary prophylaxis; among the remaining 95, 30 (31.6%) received appropriate prophylaxis, while 65 (68.4%) were prescribed SAP deemed inappropriate for one or more reasons (38.5% received a drug with a larger spectrum of activity, 9.2% a molecule with a narrower spectrum, 36.9% an incorrect dose and 76.9% a longer duration of prophylaxis). A higher number of patients in the inappropriate prophylaxis group received abdominal surgery (P = 0.001) and were admitted to a ward not participating in the ASP (P < 0.001). At multivariate analysis, being admitted to an ASP unit was the only factor independently related to having received appropriate prophylaxis. Conclusions: A low rate of adherence to local guidelines on SAP was observed, but a non-restrictive ASP can significantly impact the appropriateness of surgical prophylaxis.